PENGARUH CITRA PERUSAHAAN, EKSPEKTASI DAN KUALITAS PELAYANAN TERHADAP TERHADAP LOYALITAS NASABAH BANK BRI KC BENGKULU - Syofian Syofian (Universitas Prof. Dr. Hazairin SH, 2020)
This article was created to see anything that has a major impact on the company's image,expectations, and service quality on customer loyalty of BRI KC Bengkulu Bank. Thisresearch is associative. The type of data used is qualitative data and quantitative data withprimary data sources and secondary data. With the sampling technique using accidentalsampling technique where the customer who is the sample is the customer who is there atthe time the researcher was doing the research. In conducting research, the data collectedwill be used to solve existing problems so that the data must be truly reliable and accurate.The data methods used here include interviews, observations, questionnaires or a list ofquestions. These are techniques used by compiling closed questions and must be filled in byrespondents by selecting one of the available alternative answers. The research results areexpected to serve as a reference for the company's image, expectations and company qualityas well as loyalty and serve as input for Bank BRI to grow customer loyalty